2009
DOI: 10.1007/s12098-009-0272-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent pneumonia: Underlying cause and outcome

Abstract: The most common underlying cause of persistent pneumonia were persistent infection followed by aspiration and acquired immunodeficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 5 publications
5
36
2
3
Order By: Relevance
“…This is in agreement with many reports 7, 9, 11, 20, 24 who observed that aspiration disorders were the most frequent cause of recurrent/persistent pneumonia. Interestingly, 16 of our cases had FB aspiration.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This is in agreement with many reports 7, 9, 11, 20, 24 who observed that aspiration disorders were the most frequent cause of recurrent/persistent pneumonia. Interestingly, 16 of our cases had FB aspiration.…”
Section: Discussionsupporting
confidence: 94%
“…Notably, most of the literatures describe the etiology of recurrent/persistent pneumonia. 7–16 In the current study; 9.2% of patients with pneumonia met the definition of recurrent/persistent pneumonia, 7% for recurrent and 2.2% for persistent pneumonia. Similarly; 1–9% of patients met the criteria for recurrent/persistent in previous studies 7–16…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Foreign body aspiration, however, is by no means the most common cause of recurrent pneumonia. Recurrent or persistent pneumonia can also result from bacterial infections, gastroesophageal reflux, impaired clearance of secretions from the tracheobronchial tree as in asthma, ciliary dysmotility (primary ciliary dyskinesia), cystic fibrosis, infected bronchiectasis or secondary to an immune deficiency (Kumar et al 2009). Tumors of the tracheobronchial tree are uncommon in children, but, when present, may cause a varying degree of airway obstruction.…”
Section: Clinical Findings and Differential Diagnosismentioning
confidence: 99%